The three vehicles of Buddhist practices - Ka-rma-blo-gros (Bibliotheca Indo-Buddhica series, 1995)
Study relates to doctrines of Theravāda, Mahāyāna, and Vajrayāna - the three main vehicles (yānas) according to Tibetan Buddhist